Work and Family in the Postfeminist World - Aya Mahmoud El-Nagar (International Journal of Advanced Humanities Research)
A few decades ago, getting married and starting a family were the main objectives for young women. After being married, women's responsibility was to look after their families. The men's responsibilities included working and meeting their families' financial requirements. Nowadays, women are required to do more things than before. Young women have to be financially independent, have a career and create their own social life. In other words, women become responsible for double effort and work, as they work for pay in the public sphere and unpaid work in their houses. This means a new role and burden are added to the women’s shoulders, obliging them to act as if they are superwomen. Postfeminists blame feminists for creating a specific image of a successful woman. These social standards for successful modern women force them to fight to meet those standards. This results in an exhausting woman who suffers from self-doubt and a sense of failure if she does not conform to the modern feminist woman image.